SR-BI Interactome Analysis Reveals a Proviral Role for UGGT1 in Hepatitis C Virus Entry - Huang, Jiazhao; Yin, Han; Yin, Peiqi; Jian, Xia; Song, Siqi; Luan, Junwen; Zhang, Leiliang (Frontiers in Microbiology, 2019)
Hepatitis C virus (HCV) entry is mediated by multiple co-receptors including scavenger receptor class B, type I (SR-BI). To elucidate the interactome of human SR-BI, we performed immunoprecipitation experiment coupled with mass spectrometry analysis. UDP-glucose:glycoproteinglucosyltransferase 1 (UGGT1), a key component of calnexin cycle involved in protein glycosylation, was identified as a SR-BI-interacting protein. Silencing UGGT1 or N-glycosylation inhibitor treatment reduced SR-BI protein level. Further study demonstrated that human SR-BI was N-glycosylated at nine asparagines. Moreover, HCV entry and infection were reduced by the absence of UGGT1. Interestingly, silencing SR-BI reduced protein stability of UGGT1 and protein quality control function mediated by UGGT1. Our finding not only identified UGGT1 as a HCV host factor, but also identified a UGGT1-mediated protein folding function for SR-BI.